Gender and Modality Differences in Experiencing and Emotional Expression - Sells, David J.; Martin, Randall B. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study investigated gender and modality differences in experiencing and emotional expression. The factorial design included two levels of gender, and two levels of expression modality (public and private). All 47 participants watched and responded to questions about an emotionally provocative video. Participant responses were assessed using the Experiencing Scale, and for use of emotional words. Analyses revealed a higher level of experiencing, and more use of emotional words by women than men. Additionally, experiencing judgments of private responses were significantly higher than those of public responses. Implications for facilitation of experiencing are discussed.